The influence of Beowulf on The Lord of the Rings - Šedivá, Tereza (2007)
The thesis examines the possible influence that the heroic epic poem Beowulf had on the world of The Lord of the Rings and what features of the heroic poetry appear in Tolkien's work. It focuses on the characteristics of the heroes and the relationships between them, the representation of evil in both works and the way in which the past echoes in the present in the form of inset stories and poems